Intracranial hypotension in a breast cancer patient treated with epidural blood patches - Marie-Sophie Minot-This; Thomas Grinda; Nicolas Epaillard; David Guyon; Rita El Jawiche; Gabriel Garcia; Barbara Pistilli (CNS Oncology)
We report the case of a patient with metastatic breast cancer who presented with an orthostatic headache. After a comprehensive diagnostic workup including MRI and lumbar puncture, we maintained the diagnosis of intracranial hypotension (IH). The patient was therefore treated with two consecutive non targeted epidural blood patches, resulting in the remission of IH symptoms for 6 months. IH in cancer patients is a rarer cause of headache than carcinomatous meningitis. As the diagnosis can be made by standard examination and the treatment is relatively simple and effective, IH deserves to be better known by oncologists.